CHARACTER EDUCATION THROUGH ENGLISH MODALITY - Subur Wardoyo (Master Program in Linguistics, Diponegoro University, 2010)
The spread of English in Indonesia carries an inherent philosophy with it. This essay will focus on how the view that ‘there is no absolute truth’ is ingrained in the linguistic modality of English. Furthermore it will show how this philosophy of modality may inevitably shape a student’s character since it allows people to create the shared truths they need or to downgrade the truths of others, with all the potential positive or negative consequences. Finally this essay will also show how a visual picture, descriptive text, and dialogue could serve as teaching aids to shape a student’s character through classroom drills in such modality signifiers as modal auxiliaries, frequency adverbs, reporting frames, tenses etc. On the whole this essay relies heavily on Halliday’s Functional Grammar, von Wright’s Deontic Logic, and Hodge and Kress’s Semiotics while the topic of the picture, text and dialogue heavily centers on the mysterious Alhambra Citadel of Granada